Sport-Specific Morphology Profile: Differences in Anthropometric Characteristics between Elite Soccer and Basketball Players - Bojan Masanovic; Andjela Vukcevic; Spasoje Spaic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2018)
The aim of this study was to obtain relevant knowledge about signifi cant diff erences in some anthropometric characteristics of top soccer and basketball players. The sample included 39 male subjects divided into two subsamples. The fi rst subsample included 26 subjects, who trained in the senior selection in the Football club Vojvodina from Novi Sad, while the other subsample included 14 subjects who trained in the senior selection in the Basketball club Vojvodina, from Novi Sad. The variables sample included 20 anthropometric measures that defi ned longitudinal and transversal dimensionality of skeleton, body volume and body mass, and subcutaneous adipose tissue. The results were analysed in a statistical procedure marked as a signifi cance testing of two arithmetic means of the independent samples, a t-test at the level of signifi cance of p<0.05. It was concluded, based on these results that signifi cant diff erences occur in all variables for evaluation of longitudinal and transversal dimensionality of skeleton, as well as for body volume and body mass. When we talk about subcutaneous adipose tissue signifi cant diff erences occur in all variables except for the skinfold of the upper arm.